Analysis of Leaf Area Index of Shade Trees and Its Relationship with the Discomfort Index: A Case Study at the University of Mataram Campus - Suripto, Suripto; Rahayu, Rachmawati Noviana; Supardiono, Supardiono; Dujana, Lalu Muhammad Aby; Genggelang, Feby Ayu (Jurnal Pijar Mipa, 2025)
The development of shade trees on the Mataram University campus is intended to maintain environmental comfort, as well as add beauty. The microclimate softening function of trees is largely determined by the density of their canopies, known as the leaf area index (LAI). Various LAI measurement methods have been developed, which are generally more suitable for assessing tree productivity but less valid for assessing the ability to soften the microclimate or decrease the discomfort index (DI). This study was conducted to analyze the distribution of LAI of shade trees and their relationship with the DI on the Mataram University campus. To obtain a more valid LAI value, the leaf area variable measured was the leaf area forming the canopy, replacing the leaf area on the canopy surface, as was done in previous studies. Microclimate variables measured to determine the discomfort index (DI) were air temperature and relative humidity. The results showed that the LAI of 108 trees (33 species) spread across 9 zones within the Mataram University campus ranges from 1.2630 (very small category) to 9.6735 (very large category). The DI values under the canopy of trees ranged from 23.225 (quite comfortable category) to 26.869 (somewhat comfortable category). The relationship between LAI of shade trees and DI on the campus of Mataram University was linear and negative, with the resulting regression equation being y = 28.1204-0.4749x. If LAI increased, then DI tended to decrease; conversely, if DI increased, then LAI tended to decrease. The function of campus trees in softening the microclimate can be enhanced by improving their LAI.